Impact of Low Papaya Prices on the Socio-Economic Conditions of Farmers: an Atlas.ti Analysis - Sari, Dia Permata; Idwal B, Idwal B; Sumarni, Yenti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to comprehensively analyze the socio-economic implications of declining papaya prices on the livelihoods of farmers in Manggilan Village, Pendopo District. Method: A descriptive qualitative approach was employed through field research involving direct observation, semi-structured interviews, and document analysis. Data were systematically analyzed using Atlas.ti, a qualitative data analysis software, to extract key themes and generate coding patterns. Results: The findings indicate that low papaya prices significantly undermine farmers’ income, weaken household resilience, and adversely affect their social welfare. Several consequences were identified, including diminished financial capacity, disrupted consumption and savings patterns, reduced access to healthcare and education, and psychosocial stress. Findings: Farmers have adopted various coping strategies, such as diversifying crops, informal borrowing, and reducing household expenditures, yet these remain insufficient to offset long-term economic vulnerability. Novelty: This research uniquely integrates Atlas.ti in the socio-economic study of smallholder horticultural farmers, providing a rigorous and structured analytical framework that enhances the validity of qualitative agricultural research. Conclusion: The ongoing price decline poses a critical threat to sustainable rural development. Urgent policy interventions—such as price stabilization mechanisms, post-harvest management improvements, and cooperative marketing models—are necessary to safeguard farmer welfare. Type of Paper: Research Paper